Upaya Menciptakan Toleransi Umat Beragama di Laban Dalam Perspektif Agama Islam - Mukhlas, Abdullah Arif (FATAWA: Jurnal Pendidikan Agama Islam, 2020)
Living in harmony is the main asset to achieve a prosperous society. So that Islam teaches about harmony, condemns the existence of violence, avoids divisions. Community life that is prone to division and acts of violence is a society that has a diverse culture and culture. Laban is one of the villages with a multicultural society, so there is the potential for division and violence. However, what has happened so far is that the Laban people live their lives in harmony and peace in their daily social interactions. So there is a need for research on how tolerant the multicultural society in Laban is, whether the tolerance of multicultural communities in Laban is in accordance with the teachings of Islam. In accordance with the data collected, it resulted in the finding that the tolerance attitude of the multicultural community in Laban was based on the types of activities carried out which were divided into three, namely pure worship activities, worship activities with social values, and social activities. These three types of activities also underlie the findings about solidarity theory that is different from Ibn Khaldu's solidarity theory, namely solidarity of worship and solidarity of muasyarah. Based on the data the researchers got, the tolerance of the majority of Laban people in pure worship activities and social activities is in accordance with the teachings of Islam. Whereas worship activities that have social values, most Laban people tend to prioritize social values, even though worship activities that have social values ​​include religious activities.